IRREVERSIBLE ELECTROPORATION FOR CANCER TREATMENT: A REVIEW - Tihomir Georgiev; Georgi Todorov (Journal of IMAB, 2023)
Introduction: Prostate, pancreatic and liver cancers are a major cause of death in Europe and including Bulgaria. Some methods for treatment include the use of electric current to create pores in the cells' membranes, and can be used in combination with other techniques, while an electric field with enough strength causes irreversible electroporation (IRE) and is a separate technique. Material and methods:Search was conducted for scientific articles about electroporation and IRE. Results: Most important parameters reported in scientific articles are electric field distribution, tissue characteristics and interaction, electric pulse settings. Articles that report patient outcomes suggest several possible advantages of – retaining urinary and sexual functions, possible increase of overall survival rate, low rate of serious adverse events and promising results when applied with chemotherapy. However, there are some studies that do not corroborate these results. The technique is also used for the treatment of renal cancer, and there are researches indicating a potential for use in ovarian, cervical and breast cancer. Conclusion: Studies suggest the IRE method is safe and feasible for the treatment of prostate cancer, pancreatic cancer and liver cancer, but improvements in the protocols is needed to prevent a decrease of quality of life.